Aprendizaje por competencia en Parasitología: Learning by competence in Parasitology - Bastidas , Gilberto (2024)
The teaching of human parasitology is essential for students in health sciences, especially medicine, as it is an important public health problem with worldwide distribution. The study was a narrative review based on the search for information in Pubmed, Science Direct, Lilacs, Medline, Google academic and external sources with the descriptors: “pedagogy in parasitology”, “curriculum by competencies”, “curriculum of the parasitology”, and “teaching of parasitology”. This review article analyzes and describes the currently prevalent pedagogy for teaching it, and the characteristics of the competency curriculum that make its use as a training strategy feasible, with the purpose of contributing to the exploration of new ways of teaching parasitology and to overcome the difficulties and new challenges that must be faced in this fundamental field of medical sciences. It is concluded that the competency-based curriculum allows orienting professional training in parasitology towards a profile with proven ability to solve tasks, enhance skills and correct weaknesses.